2018
DOI: 10.1097/igc.0000000000001351
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab in Metastatic, Recurrent, or Persistent Cervical Cancer: The BC Cancer Experience

Abstract: ObjectiveWe conducted a population-based analysis of patient outcomes following treatment with bevacizumab and platinum–based chemotherapy for metastatic, recurrent, or persistent cervical carcinoma.MethodsEligible cases were identified using the BC Cancer provincial pharmacy database. Cases with small cell component or inadequate clinical follow-up were excluded. Overall response to therapy, progression-free survival (PFS), overall survival (OS), and toxicities were documented.ResultsTwenty-seven eligible cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
(18 reference statements)
1
8
1
1
Order By: Relevance
“…However, the outcomes for first-line treatment in previous clinical studies were consistent with the GOG 240 study. Compared with a median OS of 17.5 months reported by Tinker et al (8), we found a median OS of 18.2 months in primary treatment.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…However, the outcomes for first-line treatment in previous clinical studies were consistent with the GOG 240 study. Compared with a median OS of 17.5 months reported by Tinker et al (8), we found a median OS of 18.2 months in primary treatment.…”
Section: Discussioncontrasting
confidence: 84%
“…In our review of 52 patients, there were only two fistula cases reported (3.8%), one involving a genitourinary fistula and one involving a rectovaginal fistula. By comparison, Tinker et al reported a fistula rate of 3.7% (n=1) (8). This finding occurred in a frontline, real-world practice setting, and adverse events rarely led to treatment discontinuation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…According to a systematic review of 23 studies, CDDP + PTX + BEV and topotecan + PTX + BEV were likely to prolong OS compared with non–BEV-containing therapies, and CDDP + PTX + BEV had the highest probability of being the most efficacious regimen [ 112 ]. Response rates and fistula rates with CBDCA + PTX + BEV are similar to those reported with CDDP + PTX + BEV [ 114 , 115 ]. The risks and benefits of the addition of BEV to chemotherapy should be exhaustively discussed with the patient herself, taking into account the increased probability of fistula formation, especially in the case of locally persistent or recurrent disease after radiotherapy or CCRT [ 116 , 117 , 118 ].…”
Section: Bevacizumabsupporting
confidence: 78%